Tonsillitis in Focus: Clinical Features, Diagnostic Methods, and Evidence-Based Therapy - Wardana, Shira Putri; Pardoe, Lalu Dane Pemban; Yolanda, M. Rizky; Yulianti, Arwinda Febri; Habib, Philip (Jurnal Biologi Tropis, 2025)
Tonsillitis is an inflammation and infection of the palatine tonsils, typically caused by viral or bacterial pathogens. It commonly affects children aged 5 to 15 years and has a high prevalence rate in Indonesia, with chronic tonsillitis accounting for 3.8% of ENT cases. This literature review aims to explore the etiology, clinical manifestations, diagnostic approaches, and treatment options for acute tonsillitis. The method used in this paper is a literature-based descriptive analysis drawn from national and international medical sources. The main etiological agent is Group A beta-hemolytic Streptococcus, although viruses like Epstein-Barr Virus (EBV) also play a significant role. Clinical symptoms include sudden fever, sore throat, odynophagia, halitosis, dysphagia, and swollen lymph nodes. Diagnosis is established through clinical history, physical examination using Brodsky's Tonsil Scale, and confirmatory laboratory tests such as throat swab culture. Management of acute tonsillitis includes both pharmacological interventions, such as amoxicillin or clarithromycin, and non-pharmacological strategies including tonsillectomy for recurrent or chronic cases. The review concludes that proper diagnosis and evidence-based treatment are essential to prevent complications and recurrence. Furthermore, public education on personal hygiene and infection control can significantly reduce transmission. This study underscores the importance of comprehensive clinical evaluation and rational antibiotic use in managing acute tonsillitis, particularly in areas with high disease prevalence.